British periodicals and Spanish literature : mapping the Romantic canon - Flores, Cristina; Arronte, María Eugenia Perojo (Anglo-Iberian Studies, 2022)
With the main goal of contributing to a wider understanding of the presence of Spanish literature and culture in British Romanticism, this book focuses on the instrumental role played by the British periodical press in the Anglo-Spanish literary and cultural exchange in the first half of the nineteenth century. All the chapters bear witness to the contrasting and varied perception of everything Spanish, the different strategies of exploration, appropriation and rewriting of its cultural and literary tradition. Besides, they all reveal the intricate web of cultural, political and religious factors tinging the discourse of British Romantic literary critics and authors on the Spanish cultural capital.
Keywords: Spanish literature : Appreciation; British periodicals